Data on the effects of crop rotational diversity and nitrogen fertilisation on cereal yields - Smith, Monique; Bommarco, Riccardo (Swedish University of Agricultural Sciences, 2023)
Data contain standardised yields of several different cereals collected between 1958 and 2020 from 32 long-term agricultural trials across North America and Europe. Yields in tonnes per hectare were standardised against the overall mean yield per site across all treatments and years. Treatments include different levels of crop rotational diversity and nitrogen fertilisation.

This data was used in the article: Smith et al., Increasing crop rotational diversity can enhance cereal yields, Communications Earth and Environment, 2023.

See the attached documents for more information, including, ‘Metadata.txt’ for description of data codes, ‘Crop_rotation_information_desc.txt’ and ‘Crop_rotation_information.tsv’ detailing cropping sequence and mean yields of each rotation per site and ‘R_script_Smith_etal.Rmd’ to see how this data was used in the associated article.

R markdown output of the script is provided in the form of R_script_Smith_etal.pdf.

Data innehåller standardiserade skördar för olika spannmål insamlade från 1958 till 2020 från 32 långliggande jordbruksförsök i Nordamerika och Europa. Skörd per hektar standardiserades mot medelvärdet per plats över alla behandlingar och år. Behandlingarna innefattar olika nivåer av mångfald av grödor i växtföljden och kvävegödsling.

Data är grunden för analyserna i artikeln Smith et al., “Increasing crop rotational diversity can enhance cereal yields”, accepterad i Communications Earth and Environment, 2023.

Se bifogade dokumentationsfiler för beskrivning av datakoder (Metadata.txt), växtföljd och skördar (Crop_rotational_information_desc.txt och Crop_rotational_information.tsv) och R markdown-kod som använts för att analysera data (R_script_Smith_etal.Rmd).

Utmatningen från en full körning av R-skriptet kan ses i R_script_Smith_etal.pdf.
Data om effekter av mångfald av grödor i växtföljden och kvävegödsling på spannmålsskörd
Keywords: cultivation system; odlingssystem; crop rotation; växelbruk; Agricultural and aquaculture facilities; Jordbruks- och vattenbruksanläggningar; Poaceae; gräsväxter; Zea mays; majs; Hordeum vulgare; korn; Secale cereale; råg; Triticum aestivum; vete; × Triticosecale; rågveten; Avena sativa; havre; crop rotational diversity; mångfald av grödor i växtföljden; grain yield; spannmålsskörd; long-term agricultural trials; långliggande jordbruksförsök; nitrogen fertilizers; kvävegödsel; cropping sequence; växtföljd; Natural Sciences; Naturvetenskap; Ecology; Ekologi; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Farming; Areella näringar; Environment; Miljö